Observer based rotor failure compensation for biplane quadrotor with slung load - Nihal Dalwadi; Dipankar Deb; S.M. Muyeen (Ain Shams Engineering Journal, 2022)
In this study, mathematical modeling of biplane quadrotor with slung load is proposed. Performance of the biplane quadrotor is degrade while swinging of the slung load so to compensate it nonlinear observer based backstepping controller is designed that can not only handle the disturbance generated by the slung load but can also capable to tackle partial rotor failure and wind gust. Simulation study carried out by considering slung load swinging (only for quadrotor mode), wind gust, and rotor failure (for all three modes) as the external disturbance and nonlinear observer is design to estimate it. Backstepping control technique is used to design controller for all three modes of biplane quadrotor. Simulation study shows that proposed control scheme is cable to handle the disturbance generated by the different sources in quadrotor biplane.